Tailoring Strategy of Chitosan-based Hydrogel for Improving Wound Healing: A Systematic Review - Rossary, Maria Diva; Djunaedi, Jeniffer Kalyana Paramita; Prinasti Riyantoro, Teresa; Setiawati, Agustina (Trends in Sciences, 2025)
Chitosan-based hydrogels are promising wound dressing materials due to their biocompatibility, biodegradability, and ability to mimic the extracellular matrix. They have been known to promote moisture retention, prevent infection, and support cell proliferation. To enhance their properties, recent strategies include chemical and physical crosslinking, incorporation of bioactive agents, nanomaterials, and stimuli-responsive systems. Clinical studies have demonstrated the effectiveness of chitosan-based dressings in accelerating healing and reducing treatment costs, though regulatory challenges remain. Emerging innovations, by tunable their properties such as smart hydrogels and soft robotic systems, offer precise drug delivery and adaptability to wound environments. This review highlights recent advances and prospects for chitosan hydrogels as a cutting-edge technology for wound dressings with a systematic review. HIGHLIGHTS Chitosan hydrogel has ideal properties for wound dressing since it is biocompatible, hydrophilic, and has antibacterial properties Due to its reactivity on the moiety of the structure groups, chitosan is tunable modified to have some biomolecule, hormone, small compound, silver ion, or antibiotics to have specific biological activity. The future direction of chitosan hydrogel is a tunable smart hydrogel that is responsive to pH, temperature, light, and enzymes. Soft robotic chitosan-based hydrogel for wound dressings has arisen as a smart strategy by embedding controllable biological activity driven by specific responses. GRAPHICAL ABSTRACT